Safety and efficacy of plasmapheresis in treatment of acute fatty liver of pregnancy—a systematic review and meta-analysis - Siwatch, Sujata; De, Arka; Kaur, Bandhanjot; Lamba, Divjot Singh; Kaur, Simarpreet; Singh, Virendra; Periyasamy, Aravind Gandhi (Frontiers in Medicine, 2024)
Introduction: Acute fatty liver of pregnancy (AFLP) is a fatal disease occurring in 3rd trimester.The safety and efficacy of plasmapheresis/plasma exchange (PP/PE) as an adjunctive treatment in patients of AFLP has been studied. We performed systematic review and meta-analysis to estimate the clinical parameters that included mortality rates and improvement of the biochemical parameters including Liver and Renal function enzymes, coagulopathy factors of AFLP patients. Methods: We searched PubMed, Ovid MEDLINE, Cochrane, CINAHL and Scopus, ClinicalTrials.gov. RevMan statistical software was used for meta-analysis. Results: Pooled survival proportion for AFLP patients treated with PP/PE was 87.74% (95% CI: 82.84 to 91.65). Safety of PP/PE was studied by its effect on mortality. PE/PP was associated with the reduction in the mortality with pooled odds ratio of 0.51 (95% CI: 0.08 to 3.09) with I 2 =86%. Sensitivity analysis after excluding outlier study, yielded a pooled odds ratio of 0.19 (95% CI: 0.02 to 1.52) with reduced heterogeneity (I² = 63%). Biochemical parameter analysis demonstrated significant improvement post-PP/PE treatment, including decreased bilirubin (